2017
DOI: 10.1002/ente.201600715
|View full text |Cite
|
Sign up to set email alerts
|

Benzoic Acid/TEMPO as a Highly Efficient Metal‐Free Catalyst System for Selective Oxidation of 5‐hydroxymethylfurfural into 2, 5‐diformylfuran

Abstract: The combination of benzoic acid and 2,2,6,6‐teramethylpiperidin‐1‐oxyl (TEMPO) afforded an efficient catalytic system for the aerobic oxidation of 5‐hydroxymethylfurfural (HMF) into 2,5‐diformylfuran (DFF) under certain conditions. The maximum conversion of 86.7 % for HMF was obtained with a nearly 77.8 % DFF yield at 1 mmol benzoic acid and 0.4 MPa oxygen pressure in acetonitrile. The aerobic oxidation ability of HMF into DFF depended on the electron density of the organic acid skeletal structure with the car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 42 publications
(78 reference statements)
1
13
0
Order By: Relevance
“…32,33 However, there are only a few reported studies on applying N -oxyl radicals to catalyze the oxidation of HMF. 34,35 Yang et al 36 reported that benzoic acid/TEMPO obtained 86.7% conversion of HMF and 77.8% yield of DFF at 0.4 MPa O 2 in acetonitrile. Although interesting achievement was obtained by this method in the field of aerobic oxidation of HMF into DFF, it required relatively high operating pressures (0.4 MPa), high catalyst loading (50 mol %), special Teflon-lined autoclave reactors, high temperatures (up to 100 °C), and long reaction time (24 h).…”
Section: Introductionmentioning
confidence: 99%
“…32,33 However, there are only a few reported studies on applying N -oxyl radicals to catalyze the oxidation of HMF. 34,35 Yang et al 36 reported that benzoic acid/TEMPO obtained 86.7% conversion of HMF and 77.8% yield of DFF at 0.4 MPa O 2 in acetonitrile. Although interesting achievement was obtained by this method in the field of aerobic oxidation of HMF into DFF, it required relatively high operating pressures (0.4 MPa), high catalyst loading (50 mol %), special Teflon-lined autoclave reactors, high temperatures (up to 100 °C), and long reaction time (24 h).…”
Section: Introductionmentioning
confidence: 99%
“…A major reason that has led to this advance is the diversity of acid sites on the surface of solid acid catalysts and the ease of purification. [117][118][119] Although many protocols for the oxidation of furfural and HMF are described in the presence of acids, no systematic studies of the source of acid had been reported prior to the work of Choudhary et al then Lv et al [120][121][122] Before that, the oxidation of HMF in an oxidizing acid medium was reported by Descotes et al, who used 65 % nitric acid and water as solvent. The energy supply by heating or by sonication were compared, under these conditions.…”
Section: Acid Catalysismentioning
confidence: 99%
“…This result should be compared with that described by Li et al, which also demonstrated the advantage of using aromatic acids as catalysts. [121] The beneficial effect can be attributed to a π-π stacking interaction between HMF and aromatic species. We will see a little further on how this feature will be exploited with the use of carbon catalysts with a polyaromatic structure related to graphite.…”
Section: Acid Catalysismentioning
confidence: 99%
See 2 more Smart Citations